2012
DOI: 10.4081/xeno.2012.e4
|View full text |Cite
|
Sign up to set email alerts
|

Diazinon mediated biochemical changes in the African toad (Bufo regularis)

Abstract: The sublethal toxicity of diazinon to the adult African toad, Bufo regularis was assessed using an integration of biomarkers. Changes in acetylcholinesterase (AChE), corticosterone and total protein levels were assessed in the serum, brain, liver, lungs and gastrointestinal tract (GIT) and the results supported by bioaccumulation data. The biomarkers were chosen as indicators of key physiological functions: AChE for neurotoxicity, corticosterone and total protein levels as indicators of oxidative stress. Toads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…As expected, the present study demonstrates inhibition of AChE in larvae by both diazinon at a concentration of 1 mg/L and chlorpyrifos at concentrations of 0.01 and 0.1 mg/L. Inhibition of AChE activity has been documented for diazinon and chlorpyrifos on X. laevis as well as in other amphibian species (Colombo et al, 2005 ; Tongo et al, 2012 ). Although these activities were expected to increase with the level of exposure to diazinon and chlorpyrifos, no effect was observed in larvae.…”
Section: Discussionsupporting
confidence: 87%
“…As expected, the present study demonstrates inhibition of AChE in larvae by both diazinon at a concentration of 1 mg/L and chlorpyrifos at concentrations of 0.01 and 0.1 mg/L. Inhibition of AChE activity has been documented for diazinon and chlorpyrifos on X. laevis as well as in other amphibian species (Colombo et al, 2005 ; Tongo et al, 2012 ). Although these activities were expected to increase with the level of exposure to diazinon and chlorpyrifos, no effect was observed in larvae.…”
Section: Discussionsupporting
confidence: 87%
“…Amphibians are highly vulnerable to pesticides that are cholinesterase inhibitors. Many studies have indicated that pesticide reduce cholinesterase activities in amphibians (Widder & Bidwell, 2006;Khan et al, 2007;Tongo et al, 2012). Bradford et al, (2011) found low frequency (>30 %) of ChE inhibition in Rana population exposed to chlorpyrifos and considered that this was due to exposure pesticide on tadpoles.…”
Section: Discussionmentioning
confidence: 99%